CASE STUDIES IN WEB-CONTROLLED DEVICES AND REMOTE MANIPULATION - Sobh, T.; Mihali, R.; Rosca, A.; Ghimire, B.; Vovk, K.; Gosine, G.; Batra, P.; Singh, A.; Singh, S. (International Journal of Computing, 2002)
The concept of distance learning has been more and more articulated during the past few years and is expected to shortly turn into a practical education system within current high level learning institutions. The chances are that distance learning would transparently extend colleges and institutes of education, and could plausibly overtake and turn into a preferred choice of higher education, especially for adult and working students. In a supportive effort towards faster distance learning implementation and consideration, we are presenting through this material a sequence of projects that have been developed at University of Bridgeport and can serve very well in the process of distance learning education ranging from simple “hobby” style training to professional guidance material. The projects have an engineering / laboratory flavor, are part of an ongoing work of the faculty and students of the Computer Science and Engineering Department of the university, and are being presented in an arbitrary order, topics ranging from vision and sensing to engineering design, scheduling, remote control and operation.